Laminar Heat Transfer with Viscous Dissipation for Newtonian Fluids Flowing in Parallel Heated Plates with One Plate Moving. - UWAEZUOKE, M. U. (Natural Science Journal, 2019)
The paper investigates basic analytical expressions for Nusselt number with effect of viscous dissipation on the heat transfer between parallel heated plates with one plate moving, where the focus is on hydro-dynamically and thermally fully developed flow of Newtonian fluids with constant properties, neglecting the axial heat conduction in the fluids and through the walls. Thermal boundary conditions considered are: both plates kept at different constant heat fluxes, both plates kept at equal constant heat fluxes, and one plate insulated. From the analysis, new expressions for Nusselt numbers have been found, as a function of various definitions of the Brinkman number.